Consumption of vitamin and mineral supplements and its correlates among medical students in Eastern Province, Saudi Arabia - Wejdan M Al-Johani; Kasim M Al-Dawood; Moataza M Abdel Wahab; Haneen A Yousef (Wolters Kluwer Medknow Publications, 2018)
Background: Although vitamin and mineral supplements are popular in many countries, few studies have documented their use among college students. Moreover, there is not much national data on the use of supplements by Saudi medical students. The aim of this study was to determine the prevalence of the use of vitamin and mineral supplements by female medical students at Imam Abdulrahman Bin Faisal University (IAU) in Dammam, Saudi Arabia, and to identify characteristics associated with the use of supplements in this population. Materials and Methods: For this cross-sectional study, all female medical students at IAU in Dammam, Saudi Arabia, were approached during September to November 2016. Results were presented as frequency distribution. Chi-square test and logistic regression analysis were performed to determine factors associated with supplement use; P < 0.05 was considered statistically significant. Results: Completed questionnaires were returned by 474 students (response rate of 77%). The prevalence of the use of vitamin and mineral supplements was 44.6%; Vitamin D was the most commonly used supplement. Association of supplement use with a higher family income and the habit of regular exercise was statistically significant. However, this use of supplements was not significantly associated with smoking or marital status. Conclusion: The use of supplements, particularly Vitamin D, by female medical students was 44.6%. The highest percentage of users belonged to families with higher incomes and had the habit of exercising regularly.